FINDING BEST METHOD FOR CHILD PRISONER MEDIATION IN THE PROCESS OF TRANSITION BACK INTO COMMUNITY IN INDONESIA - Pan Lindawaty Sewu; Yohanes Hermanto Sirait; Ai Permanasari (Faculty of Law, Universitas Sebelas Maret, 2018)
Children are the next generation of a state, no exception for child prisoner. There is limitless future for all children in the world, including Indonesia. The problem is, some of child prisoner transform into adult prisoner because their life background makes them hard to rejoin or accepted in any social community. This article aims to examine the best method for child prisoner mediation based on principle of for the best interest of the child. This article is a sociological juridical research, using secondary data and field data as addition. The data collected by using library research and analyzed qualitatively. This article finds that child prisoner mediation will help to provide opportunity for child prisoner and family members or other stakeholder to meet, with the help of a mediator, before release to have an open, honest, and sincere dialogue to prepare for the transition back into the community. The best interest of the child remains as core principle without decreasing other necessary principle in succussing mediation process. Child prisoner mediation is a process of mediation held especially for child prisoner and will restore the future of child prisoner in Indonesia.Keywords: child prisoner; community; mediation